Association of BAK1 single nucleotide polymorphism with a risk for dengue hemorrhagic fever. Issue 1 (December 2016) - Dang, Tran; Naka, Izumi; Sa-Ngasang, Areerat; Anantapreecha, Surapee; Wichukchinda, Nuanjun; Sawanpanyalert, Pathom; Patarapotikul, Jintana; Tsuchiya, Naoyuki; Ohashi, Jun
Abstract Background Dengue hemorrhagic fever (DHF) is a severe life-threatening form of dengue infection. Low platelet count is one of the characteristic clinical manifestations in patients with severe dengue. However, little is known about genetic factors in the host that cause low platelet count in patients with dengue. Methods A previous genome-wide association study of hematological and biochemical traits identified single nucleotide polymorphisms (SNPs) associated with low platelet count in healthy subjects. To examine the possible association of these SNPs with DHF, 918 Thai patients with dengue [509 patients with DHF and 409 with dengue fever (DF)] were genotyped for five SNPs: rs5745568 inBAK1, rs6141 inTHPO, rs6065 inGP1BA, rs739496 inSH2B3, and rs385893 inRCL1 . In addition, rs4804803 inCD209, that has been reported to be associated with dengue infection, was also genotyped to examine if rs4804803 affects the association detected in this study. Results The allele frequencies of each SNP were compared between the DHF and DF groups. Among the five SNPs, the G allele of rs5745568 inBAK1 was significantly associated with a risk for DHF [P = 0.006 and crude odd ratio (95 % confidence interval) = 1.32 (1.09–1.60)]. The association of this allele with DHF was also significant in a logistic regression analysis adjusted for age, sex, hospital (i.e., geographic region), immune status (i.e., primary or secondary infection), and virus serotype [P = 0.016 and adjusted odd ratio (95 % confidence interval) = 1.29 (1.05–1.58)]. The result was not influenced by rs4804803 [P = 0.0167 and adjusted OR (95 % CI) = 1.29 (1.05–1.58)]. No other SNPs including rs4804803 showed significant association. Conclusions The low-level constitutive production of platelets caused by the G allele of rs5745568 seems to increase the risk of bleeding in dengue infection. Our results suggest that BCL-2 homologous antagonist/killer (BAK) protein, encoded byBAK1, plays a crucial role in the pathogenesis of DHF.